(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
This research article explores the eco-consciousness in Jim Corbett’s writings, emphasizing his deep connection to nature and his commitment to wildlife conservation highlighting his dual role as a hunter and conservationist, revealing his empathy for animals and understanding of their ecological significance. While Corbett’s tales are often thrilling accounts of hunting man-eaters, they also contain profound reflections on environmental balance and respect for all species. Written at a time when the modern conservation movement was in its infancy, Corbett’s works showcase a forward-thinking approach to ecological preservation, advocating for a shift from anthropocentrism to a more inclusive view of nature’s intrinsic value. This literary analysis underscores how Corbett’s blend of adventure storytelling with environmental insight remains relevant, especially in today’s demanding context of environmental crisis. Through an ecocritical lens, this article argues that Corbett’s writing serves as a reminder of the importance of sustainable and ethical stewardship of nature.